2019
DOI: 10.1101/770297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of CAR-T Cell Therapy for B-ALL Using a Point-of-Care Approach

Abstract: AbstractRecently approved by the FDA and European Medicines Agency, CAR-T cell therapy is a new treatment option for B-cell malignancies. Currently, CAR-T cells are manufactured in centralized facilities and face bottlenecks like complex scaling up, high costs and logistic operations. These difficulties are mainly related to the use of viral vectors and the requirement to expand CAR-T cells to reach the therapeutic dose. In this paper, by using Sleeping Beauty-mediated genetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In particular, minimally manipulated CAR T cells kept in culture for less than 24 h have demonstrated some level of antitumor activities in animal models and in human subjects. The optimization of this approach could simplify CAR‐T manufacturing and has the potential to drastically decrease the overall cost [129, 130].…”
Section: Car T‐cell Manufacturingmentioning
confidence: 99%
“…In particular, minimally manipulated CAR T cells kept in culture for less than 24 h have demonstrated some level of antitumor activities in animal models and in human subjects. The optimization of this approach could simplify CAR‐T manufacturing and has the potential to drastically decrease the overall cost [129, 130].…”
Section: Car T‐cell Manufacturingmentioning
confidence: 99%
“…Stimulating and culturing T cells for long period of time can lead to terminal differentiation. To overcome this limitation, and in order to optimize the phenotype of therapeutic T cells, some groups started reducing the culturing time 13 , 14 or adding cytokines that can help retaining a more memory and stem phenotype. Such cytokines include, but are not restricted to, IL-7, IL-15 15 and IL-21.…”
Section: Key Steps For Car Cell Manufacturingmentioning
confidence: 99%
“…Their group showed that isolation of PBMCs and genetic modification can be obtained in 4 h, generating CAR-T cells with in vivo activity. Cells generated with this rapid point of care compatible protocol were shown to have the same potency of CAR-T cells generated following in vitro expansion in pre-clinical models [ 139 ], indicating that CAR-T cells could be generated with minimal manipulation at the site of treatment using low cost protocols, especially in the allogeneic setting.…”
Section: New Routes For Gene Transfer: Bringing the Car To The Celmentioning
confidence: 99%